Pathways for building urban resilience to climate change in Oman. Issue 5 (4th July 2019) - Al-Awadhi, Talal; Charabi, Yassine; Choudri, B.S.
ABSTRACT: The Sultanate of Oman is highly vulnerable to climate change. Recent experiences with Cyclone Gonu in 2007, Phet in 2010 and Mekunu 2018, show the potential impact of extreme climatic events on urban areas, with a high loss of life, destruction of infrastructure and economic damage. Despite Oman facing multiple hazards and risks from climate change, no policies or strategies have been specifically designed to build climate resilience for urban cities. This study aims to raise awareness among policymakers to develop a national policy framework towards addressing urban climate change adaptation and resilience. It suggests several pathways for the country based on a review of previous studies and interviews with key stakeholders. Identified pathways include generation of knowledge on climate change, capacity building, improved governance, and planning.